y+y+y+y=39+y:y
219,1+y:y<yx2+yx4-y<230,2-y+y
219,1 + y:y < y \(\times\) 2 + y \(\times\) 4 - y < 230,2 - y + y
219,1 + 1 < y \(\times\) 2 + y \(\times\) 4 - y \(\times\) 1 < 230,2 - ( y - y)
210,1 < y \(\times\) ( 2 + 4 - 1) < 230,2
210,1 < y \(\times\) 5 < 230,2
210,1 : 5 < y < 230,2: 5
42,02 < y < 46,04
Tìm y biết y-36= y:y +1
\(y-36=y\div y+1\)
\(y-36=1+1\)
\(y-36=2\)
\(y=2+36\)
\(y=38\)
Vậy \(y=38\)
\(y-36=y:y+1\)
\(y-36=1+1\)
\(y-36=2\)
\(y=2+36\)
\(y=38\)
If the average of y:y + 2 and y + 4 is 12.Then y =
tìm y:y + 23 = 6 x y +17
y + 23 = 6 x y + 17
=> 5 x y = 6
=> y = 6/5
a, Tìm y: y x 20 + 16 x y = 972 |
\(y.\left(20+16\right)=972\Leftrightarrow36y=972\Leftrightarrow y=27\)
y x (20+ 16) = 972
y x 36 = 972
y = 972 : 36
y = 27
Tìm y:
y x 3,2 + y x 6,8 = 125,68-99
\(\Rightarrow y\times\left(3,2+6,8\right)=26,68\\ \Rightarrow y\times10=26,68\\ \Rightarrow y=26,68:10\\ \Rightarrow y=2,668\)
Bài 3:Tìm y:y+19₫84 36-y₫14
em viết anh ko hiểu nổi
2/ Tìm y:
y + \(\dfrac{1}{3}\) x 4 = 12 \(\dfrac{2}{5}\) + y = \(\dfrac{12}{35}\) x \(\dfrac{14}{9}\)
\(y=12-\left(\dfrac{1}{3}\times4\right)=12-\dfrac{4}{3}=\dfrac{32}{3}\)
\(y=\left(\dfrac{12}{35}\times\dfrac{14}{9}\right)-\dfrac{2}{5}=\dfrac{8}{15}-\dfrac{2}{5}=\dfrac{2}{15}\)
a) \(y+\dfrac{1}{3}\times4=12\)
\(y+\dfrac{1}{3}=12:4\)
\(y+\dfrac{1}{3}=3\)
\(y=3-\dfrac{1}{3}\)
\(y=\dfrac{8}{3}\)
b) \(\dfrac{2}{5}+y=\dfrac{12}{35}\times\dfrac{14}{9}\)
\(\dfrac{2}{5}+y=\dfrac{8}{15}\)
\(y=\dfrac{8}{15}-\dfrac{2}{5}\)
\(y=\dfrac{2}{15}\)
(2xy: x^2 - y^2 + x-y : 2x + 2y) : x+y:2x + y:y-x
x^2+3xy: x^2 - 9y^2 + 2x^2 - 5xy- 3y^2 : 6xy - x^2- 9y^2 - x^2+ xz + xy + yz: 3yz - x^2 - xz + 3xy